Prevalence and factors associated with hypertension among adults in rural Sylhet district of Bangladesh: a cross-sectional study - Salahuddin Ahmed; Dustin G Gibson; Rasheda Khanam; Sayedur Rahman; Gulam Muhammed Al Kibria; Jafar Raza Rizvi Syed; Ahad Mahmud Khan; Syed Mamun Ibne Moin; Malathi Ram; George Pariyo; Abdullah H. Baqui (BMJ Open)
Objectives Low-income and middle-income countries are undergoing epidemiological transition, however, progression is varied. Bangladesh is simultaneously experiencing continuing burden of communicable diseases and emerging burden of non-communicable diseases (NCDs). For effective use of limited resources, an increased understanding of the shifting burden and better characterisation of risk factors of NCDs, including hypertension is needed. This study provides data on prevalence and factors associated with hypertension among males and females 35 years and older in rural Bangladesh.Methods This is a population-based cross-sectional study conducted in Zakiganj and Kanaighat subdistricts of Sylhet district of Bangladesh. Blood pressure was measured and data on risk factors were collected using STEPS instrument from 864 males and 946 females aged 35 years and older between August 2017 and January 2018. Individuals with systolic blood pressure of ≥140 mm Hg or diastolic blood pressure of ≥90 mm Hg or taking antihypertensive drugs were considered hypertensive. Bivariate and multivariate analyses were performed to identify factors associated with hypertension.Results The prevalence of hypertension was 18.8% (95% CI 16.3 to 21.5) and 18.7% (95% CI 16.3 to 21.3) in adult males and females, respectively. Among those who were hypertensive, the prevalence of controlled, uncontrolled and unaware/newly identified hypertension was 23.5%, 25.9% and 50.6%, respectively among males and 38.4%, 22.6% and 39.0%, respectively among females. Another 22.7% males and 17.8% females had prehypertension. Increasing age and higher waist circumference (≥90 cm for males and ≥80 cm for females) were positively associated with hypertension both in males (OR 4.0, 95% CI 2.5 to 6.4) and females (OR 2.8, 95% CI 2.0 to 4.1).Conclusions In view of the high burden of hypertension and prehypertension, a context-specific scalable public health programme including behaviour change communications, particularly to increase physical activity and consumption of healthy diet, as well as identification and management of hypertension needs to be developed and implemented.